Oral contraceptive use by formulation and endometrial cancer risk among women born in 1947-1964: the Nurses’ Health Study II, a prospective cohort study - Burchardt, Norah Ana; Shafrir, Amy L.; Kaaks, Rudolf; Tworoger, Shelley S.; Turzanski Fortner, Renée (European journal of epidemiology, 2021)
Oral contraceptives (OCs) have been associated with long-term lower endometrial cancer risk; relatively little is known about associations with more recent OC formulations and associations with longer-term risk. A total of 107,069 women from the Nurses’ Health Study II recalled OC use from age 13 to baseline (1989); biennial questionnaires updated data on OC use until 2009. OCs were classified by estrogen and progestin type, dose, and potency based on reported brand. 864 incident endometrial cancer cases were identified through 2017. Multivariable Cox proportional hazards models estimated hazard ratios (HR) and 95% confidence intervals [95% CI] for the association of OC use with endometrial cancer risk. OC use was associated with lower endometrial cancer risk (ever use, HR 0.77 [95% CI 0.65-0.91]; >10 years of use, 0.43 [0.32-0.58] vs. never OC use). Inverse associations for duration were evident regardless of time since last use. Longer durations (> 5 years) of ethinyl estradiol (0.52 [0.41-0.67]) and second-generation progestins (0.43 [0.30-0.61]), both versus never use, were more strongly associated with lower risk than mestranol (0.66 [0.50-0.88], p-het = 0.01) and first-generation progestins (0.62 [0.49-0.78], p-het = 0.03). Inverse associations were generally observed for cross-classified cumulative average estrogen and progestin dose and potency (< vs. ≥ median; ever use vs. never OC use), with the exception of high estrogen and low progestin dose. OCs were associated with lower endometrial cancer risk, independent of time since last use. Use of ethinyl estradiol and second-generation progestins were more strongly inversely associated with risk compared with older formulations.
Published online: 17 December 2020
Gesehen am 15.01.2024